If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7g(-3h + 1) = 0 Reorder the terms: 7g(1 + -3h) = 0 (1 * 7g + -3h * 7g) = 0 (7g + -21gh) = 0 Solving 7g + -21gh = 0 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), '7g'. 7g(1 + -3h) = 0 Ignore the factor 7.Subproblem 1
Set the factor 'g' equal to zero and attempt to solve: Simplifying g = 0 Solving g = 0 Move all terms containing g to the left, all other terms to the right. Simplifying g = 0Subproblem 2
Set the factor '(1 + -3h)' equal to zero and attempt to solve: Simplifying 1 + -3h = 0 Solving 1 + -3h = 0 Move all terms containing g to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -3h = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -3h = 0 + -1 -3h = 0 + -1 Combine like terms: 0 + -1 = -1 -3h = -1 Add '3h' to each side of the equation. -3h + 3h = -1 + 3h Combine like terms: -3h + 3h = 0 0 = -1 + 3h Simplifying 0 = -1 + 3h The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
g = {0}
| 81-x=93-x | | 2a+2=a+4 | | 79-(101-5y)=2(101-5y)+y | | 6.5(x-4)=-0.5x+30 | | 5=(x+8) | | -5x+6y=30 | | 19x=12x | | 11x+2=5x+10+58 | | -5-x=1+2x | | 4d=7-7 | | 8x+2+70+60= | | -5(a-6)+2a=9 | | (3x-6y-1)+(-x+y+10)= | | 3w+10=-3+8w-9w | | 4(2y+1)-2y=-26 | | 1/3(102-12c)=5(3c+10) | | 5x-x-3=2x+6 | | M-3=7m-21 | | 4n-(7-6n)=13 | | 6x+3=3(2x+3) | | 2x-11=23 | | 3x=52 | | (9x-8y-11)-(5x-9y+1)= | | -8=1.3x+x | | 10=-2.3(4x+5) | | 18b-21=15b+3 | | 7x-[-5]=-9 | | 4=2.3x+9-1.3x | | 6m=2m-8 | | 2x(28)=x+4 | | 26x+24=-39x-6 | | -6x-9x+11= |